Sinonasal Myxoma Extending into the Orbit in a 4-Year Old: A Case Presentation - Purrinos, Julian A; Younis, Ramzi (Archives of Case Reports, 2024)
Background: Sinonasal myxomas are exceptionally rare benign tumors in pediatric patients. This report presents the case of a 4-year-old boy diagnosed with a sinonasal myxoma extending into the right orbit. Case presentation: The patient’s clinical presentation included moderate-angle esotropia and ocular torticollis. Advanced imaging revealed an expansile lesion in the right posterior ethmoid cavity with orbital involvement. The differential diagnosis considered included malignancies such as rhabdomyosarcoma and lymphoma, as well as benign neoplasms and inflammatory changes. A biopsy confirmed the diagnosis of sinonasal myxoma. The patient underwent a wide local resection performed by a multidisciplinary team, leading to a confirmed histopathological diagnosis of sinonasal myxoma. Conclusion: This case highlights the diagnostic challenges and the importance of thorough clinical and radiologic evaluation in pediatric patients with unusual ocular symptoms. The report underscores the need for a multidisciplinary approach in managing rare neoplasms such as sinonasal myxomas.